PERUBAHAN BEBERAPA SIFAT KIMIA DAN BIOLOGI ULTISOL DAN SERAPAN HARA N P K SERTA PRODUKSI TANDAN BUAH SEGAR YANG DIBERI LCPKS - Marlina, Marlina; Napoleon, Adipati; Budianta, Dedik (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2018)
This research titled “Change Some Properties of Chemical and Biological Ultisol and Nutrient Uptake of N P K Plant and Production of Fresh Fruit Bunches Marked Palm Oil Mill Effluent”. This research held from April till December 2014. The results showed that the application LCPKS can improve nutrient P , but has not been a significant influence on the chemical properties of the other on the ground in oil palm plantations. Liquid Waste Award mills are capable of increasing the population of micro- organisms in the soil first and third day of observation.  Results of weighing directly on the ground show that the weight of fresh fruit bunches (TBS) reached an average of 30.45 kg per bunch in the treatment on non LCPKS and weighs TBS averaged 21.48 kg per bunch . This shows that LCPKS can increase the weight of TBS as well as production